Tissue-Engineered Tracheal Reconstruction - Se Hyun Yeou; Yoo Seob Shin (Biomimetics)
Tracheal reconstruction remains a formidable clinical challenge, particularly for long-segment defects that are not amenable to standard surgical resection or primary anastomosis. Tissue engineering has emerged as a promising strategy for restoring the tracheal structure and function through the integration of biomaterials, stem cells, and bioactive molecules. This review provides a comprehensive overview of recent advances in tissue-engineered tracheal grafts, particularly in scaffold design, cellular sources, fabrication technologies, and early clinical experience. Innovations in biomaterial science, three-dimensional printing, and scaffold-free fabrication approaches have broadened the prospects for patient-specific airway reconstruction. However, persistent challenges, including incomplete epithelial regeneration and mechanical instability, have hindered its clinical translation. Future efforts should focus on the design of modular biomimetic scaffolds, the enhancement of immunomodulatory strategies, and preclinical validation using robust large animal models. Sustained interdisciplinary collaboration among surgical, engineering, and biological fields is crucial for advancing tissue-engineered tracheal grafts for routine clinical applications. Within this context, biomimetic approaches, including three-dimensional bioprinting, hybrid materials, and scaffold-free constructs, are gaining prominence as strategies to replicate the trachea’s native architecture and improve graft integration.